Comparison of population-genetic structuring in congeneric kelp- versus rock-associated snails: a test of a dispersal-by-rafting hypothesis - Nikula, Raisa (Blackwell Publishing Ltd, 2011)
Phylogeographic studies indicate that many marine invertebrates lacking autonomous dispersal ability are able to achieve trans-oceanic colonization by rafting on buoyant macroalgae. However, less is known about the impact of rafting on on-going population-genetic connectivity of intertidal species associated with buoyant macroalgae. We hypothesize that such species will have higher levels of population-genetic connectivity than those exploiting nonbuoyant substrates such as rock. We tested this hypothesis by comparing nuclear multilocus population-genetic structuring in two sister topshell species, which both have a planktonic larval phase but are fairly well segregated by their habitat preference of low-tidal bull-kelp holdfasts versus mid-to-low tidal bare rock. We analyzed population samples from four sympatric sites spanning 372 km of the east coast of southern New Zealand. The sampled region encompasses a 180 km wide habitat discontinuity and is influenced by a stable, northward coastal current. The level of connectivity was high in both species, and neither of them showed significant correlation between genetic and geographic distances. However, a significant negative partial correlation between genetic distance and habitat discontinuity was found in the rock-associated species, and estimates of migrant movement between sites were somewhat different between the two species, with the kelp-associated species more often yielding higher estimates across the habitat discontinuity, whereas the rock-associated species more often exhibited higher estimates between sites interspersed by rock habitats. We conclude that for species with substantial means of autonomous dispersal, the most conspicuous consequence of kelp dwelling may be enhanced long-distance dispersal across habitat discontinuities rather than a general increase of gene flow.